THE ROLE OF KNOWLEDGE SHARING IN ENHANCING INNOVATION PERFORMANCE AMONGST COMMERCIAL BANKS IN KENYA - Odero, Jackline Akoth; wanyama, Ezekiel Wechuli (Machakos University Press, 2021)
Modern organizations are exposed to challenges arising due to a complex and an unpredictable competitive environment. Over the years, knowledge sharing has become a major strategic necessity that organizations require to succeed in the global business atmosphere. Knowledge as one of the most vital assets of all corporate organizations must be effectively shared in order to achieve sustainable competitive advantage. The study sought to examine the role of knowledge sharing in enhancing innovation performance amongst Commercial banks in Kenya. The study adopted descriptive survey research design. This study targeted 15 commercial banks in Kakamega County. Structured questionnaires were used to collect data targeting fourty five managers who were purposively sampled. A census study was done. Data was analyzed using descriptive and inferential statistics. For descriptive statistics mean and standard deviation were used. For inferential statistics the study utilized Pearson’s product moment correlation and simple regression analysis. Data was presented in form of tables. Study findings revealed that knowledge sharing had a positive and significant influence on innovation performance. The study recommends that bank managers should pay keen interest to knowledge sharing strategies in order to enhance innovation performance. The paper contributes to scholarly debate on the role knowledge sharing plays in enhancing innovation performance. The results may assist managers to facilitate knowledge sharing in commercial banks in order to boost innovation performance.
Keywords: Commercial Banks; Knowledge Sharing; Innovation Performance